Evolution of malaria in pregnancy control: Jhpiego's 10‐year contribution. (23rd June 2015) - Roman, Elaine; Ngindu, Augustine; Orji, Bright; Zoungrana, Jérémie; Robbins, Sarah; Brieger, William
Abstract: Malaria continues to be a life‐threatening illness throughout Sub‐Saharan Africa, with pregnant women and children being particularly vulnerable and an estimated 10 000 women and 200 000 newborns dying each year as a result of malaria in pregnancy (MIP). Since 2004, WHO has supported a three‐pronged MIP approach: (1) intermittent preventive treatment with sulfadoxine‐pyrimethamine; (2) use of insecticide‐treated bed nets; and (3) effective case management. The present article identifies benchmarks in Jhpiego's 10‐plus years of MIP experience at the regional and national levels that have contributed to its global MIP leadership and aligned programs and policies with global approaches toward malaria elimination. As countries continue to develop and expand MIP programming, support will continue to be essential in the following eight MIP program areas: integration, policy, capacity development, community engagement, quality assurance, commodities, monitoring and evaluation, and financing.